Benefit of Mach number and expansion level on the flow development in a cylindrical tube diameter of 18 mm - Khan, Sher Afghan; Baig, Maughal Ahmed Ali; Ridwan, R; Rayid, Muneer; Suheel, J I; Faheem, Mohammed (Elsevier Ltd, 2021)
In this paper, experiments are performed at high Mach numbers to examine the flow control effect located in the separated region at 6.5 mm from the central jet. A circular orifice is placed in the wake region to manipulate the base flow to boost the wake area’s pressure and ultimately reduce the base drag. The study also investigates the impact of micro-jets on the stream of the tube. Accordingly, tests are conducted using C-D nozzles fabricated at Mach 1.87, 2.2, and 2.58. Flow generated from these nozzles is exhausted in a duct whose diameter is 18 mm. The results show that for duct length 6D and above, the flow field inside the duct becomes oscillatory, whereas such fluctuations are not noticed when duct size is less than 4D. Dynamic control shows mixed trends when jets are operating at design NPR or under the impact of favorable pressure. And within reattachment length, active flow control is not able to impact the flow pattern. When nozzles are running underneath, over-expansion and flow control are initiated; it decreases the duct’s pressure. The smallest duct size essential for the stream to continue connected appears to be 1D for Mach 1.87 and Mach 2.2 and 2.58; this requirement is 2D.